2023
DOI: 10.1038/s41598-023-36451-3
|View full text |Cite
|
Sign up to set email alerts
|

Knocking out alpha-synuclein in melanoma cells downregulates L1CAM and decreases motility

Abstract: The Parkinson’s disease (PD) associated protein, alpha-synuclein (α-syn/SNCA), is highly expressed in aggressive melanomas. The goal of this study was to reveal possible mechanism(s) of α-syn involvement in melanoma pathogenesis. Herein, we asked whether α-syn modulates the expression of the pro-oncogenic adhesion molecules L1CAM and N-cadherin. We used two human melanoma cell lines (SK-MEL-28, SK-MEL-29), SNCA-knockout (KO) clones, and two human SH-SY5Y neuroblastoma cell lines. In the melanoma lines, loss of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…We measured an increase in the percentage of cells with micronuclei at baseline in the αSyn KO condition, that was also present 6- and 24-hours post rDNA DSB induction with I-PpoI (Figure 7B). We also measured proliferation, migration, and invasion to determine downstream contributions of αSyn function to these cellular phenotypes, since previous studies have found dysregulation of various growth measurements in αSyn KO cells 40, 59 . SK-Mel28 αSyn KO cells also exhibited impaired proliferation, migration, and invasion capabilities compared to control and αSyn KI-rescue cells (Figure 7C), suggesting that αSyn-mediated rDNA DSB repair is important for cell survival and growth.…”
Section: Resultsmentioning
confidence: 99%
“…We measured an increase in the percentage of cells with micronuclei at baseline in the αSyn KO condition, that was also present 6- and 24-hours post rDNA DSB induction with I-PpoI (Figure 7B). We also measured proliferation, migration, and invasion to determine downstream contributions of αSyn function to these cellular phenotypes, since previous studies have found dysregulation of various growth measurements in αSyn KO cells 40, 59 . SK-Mel28 αSyn KO cells also exhibited impaired proliferation, migration, and invasion capabilities compared to control and αSyn KI-rescue cells (Figure 7C), suggesting that αSyn-mediated rDNA DSB repair is important for cell survival and growth.…”
Section: Resultsmentioning
confidence: 99%
“…The accumulation of α-synuclein oligomers has been described as a hallmark of PD. It is also observed in malignant melanoma, where it contributes to the increased proliferation of tumor cells [5,[82][83][84].…”
Section: α-Synuclein and Melanomamentioning
confidence: 96%